Key Account Management : the Definitive Guide - Woodburn, Diana; McDonald, Malcolm (Chichester : Wiley, 2012)
""This book is crammed with distilled, practical wisdom for key account managers and their directors. Organizations claiming to practise key account management should equip everyone involved with a copy, so they really understand what they are supposed to be doing. Anything less is just old-fashioned selling."" Developing successful business-to-business relationships with more customers in highly competitive markets requires processes and skills that go beyond traditional selling activity. The very best state-of-the-art strategies are set out clearly in this book by intentionally known autho.
4.3 Managing relationships4.3.1 Multilevel relationships; 4.3.2 Avoiding relationship traps; Summary; 5 The buyer perspective; Introduction; 5.1 The purchasing context; 5.1.1 Customer drivers; 5.1.2 Cost reduction; 5.1.3 Risk reduction; 5.2 Buying company strategies; 5.2.1 Strategy independence; 5.2.2 Strategy direction matrix; 5.2.3 Supply chain integration; 5.2.4 Matching strategies; 5.2.5 Supplier delusions; 5.2.6 Trust; 5.3 Balance of power; Summary; 6 Key account profitability; Introduction; 6.1 Profitability in the context of key accounts.
6.1.1 Sustainable competitive advantage and key accounts.
Includes bibliographical references and index.
Print version record.
Keywords: Marketing -- Key accounts; Selling -- Key accounts; BUSINESS & ECONOMICS -- General; Business; Key account management; Marketing -- Key accounts; Selling -- Key accounts; BUSINESS & ECONOMICS -- Marketing -- Industrial; Marketing -- Key accounts; Selling -- Key accounts; Electronic books